Psychological Resilience of Employees in Adversity Quotient: Malaysian Perspective in Facing Challenges - M.F, Lee (uthm, 2023)
Psychological resilience is the ability to manage psychologically or emotionally with a catastrophe or to swiftly recover to pre-crisis position. Adversity is one of the most important abilities for psychological resilience. Workers in the twenty-first century must be able to deal with adversity in a challenging work environment, especially during a pandemic. The purpose of this study was to determine the level of adversity quotient among Malaysian employees during the pandemic period. Different employees' ability adversity quotients have also been compared in terms of gender, race, and age. This study's design is a cross-sectional survey with 585 respondents from all around Malaysia selected using a convenient sampling technique. A modified version of Dr. Paul G. Stoltz's Adversity Response Profile was employed as instrument in this study. The data was then analysed with the sum, median, mean, standard deviation, independent-sample t-test, and logistic regression. The findings of the study show that the majority of employees have a high adversity quotient score. In terms of gender, men employees tend to score higher than female employees. Employees aged 50 and over excel those aged 26 and below. However, the adversity quotient score for employees of different races is not significantly different. Employers should eventually take serious concern by implementing the appropriate intervention programme or policy aimed at potential employees in order to overcome their shortcoming in the adversity quotient and, more importantly, to enhance the employee's ability to face challenges in order to drive the company's mission and vision.